Immunogenicity and safety of live attenuated and recombinant/inactivated varicella zoster vaccines in people living with HIV: A systematic review - Valentina Carta; Lucia Mangeri; Giorgio Tiecco; Emanuele Focà; Eugenia Quiros-Roldan; Maria Antonia De Francesco (Human Vaccines & Immunotherapeutics)
Few papers focus their attention on VZV vaccination effectiveness among people living with HIV (PLWH). Flanking the live attenuated vaccine (VZL) available, a newly recombinant vaccine (RZV) was recently introduced and approved for HZ prevention among adults. PLWH represents a population on which a particular attention should be applied, in order to guarantee the vaccine efficacy and safety. We performed a literature search in USNLM, PubMed, PubMed Central, PMC and Cochrane Library. From all the publications found eligible, data were extracted and processed per population, vaccine type, immunogenicity and ADRs. The review of the 13 included studies shows that both RZV and VZL are immunogenic and have an acceptable safety profile in adults and children living with HIV. However, given the lack of research available about vaccine efficacy in preventing VZV and HZ in PLWH, additional studies need to be performed, in order to achieve a full completeness of data.